GAMBARAN PENGETAHUAN ORANG TUA SISWA KELAS I TENTANG KARIES PADA GIGI MOLAR SATU PERMANEN - Irma Syafriani; Kirana Patrolina Sihombing (Jurnal Kesehatan Gigi, 2019)
Permanent first molars are the largest teeth and only eruption after the growth and development of the jaw is enough. About all children school around the world have suffered dental caries, and the highest are found in Asia and Latin America. The type of research is a descriptive study with the goal to describe the knowledge of parents about caries in permanent first molars at SD Negeri 104238 Telaga Sari Kec. Tanjung Morawa in 2018. A total of 30 respondents selected by the proposive sampling method measured their parents' knowledge about caries in the permanent first molars and caries in the child's permanent first molars. The results is as many as 70% of parents of class I students had good knowledge, as many as 89.67% of class I students had permanent first molars that had grown, and 46.77% of grade I students had permanent first molars that had been affected by caries. The level of knowledge of parents of class I students about caries in permanent first molars at SD Negeri 104238 Telaga Sari in Tanjung Morawa in 2018 has been categorized well even though there is still permanent first molars caries in class I students.